On The Dependent Elements of Reveres Bimultipliers - Mahmood, Auday H.; Harjan, Eqbal J. (Iraqi Journal of Science, 2022)
The objective of this paper is to study the dependent elements of a left (right)reverse bimultipliers on a semiprime ring. A description of dependent elements ofthese maps is given. Further, we introduce the concept of double reverse ( , )-Bimultiplier and look for the relationship between their dependent elements.